SAT0261 Certolizumab pegol serum levels ≥20 mg/l are associated with treatment response in patients with axial spondyloarthritis. data from the nor-dmard study. (12th June 2018) - Gehin, J.E.; Syversen, S.W.; Warren, D.J.; Goll, G.L.; Sexton, J.; Strand, E.K.; Kvien, T.K.; Bolstad, N.; Lie, E.
Abstract : Background: Measurement of serum drug levels can help clinicians tailor treatment with TNF-inhibitors. An association between certolizumab pegol (CP) serum levels and response has previously been found in patients (pts) with rheumatoid arthritis. 1 Data for pts with axial spondyloarthritis (axSpA) are lacking. Objectives: To examine the association between serum CP levels and treatment response in pts with axSpA and to identify a therapeutic target level. Methods: Patients with a clinical diagnosis of axSpA starting standard treatment with CP included in the NOR-DMARD study with biobank sample at 3 months follow-up, were included in the present analyses. Serum drug levels (non-trough) were analysed with an in-house immunofluorometric assay automated on the AutoDELFIA immunoassay platform. Associations between CP level and improvement in ASDAS-CRP and response (defined as ASDAS clinically important improvement (CII)) were assessed by multivariable linear and logistic regression (adjusting for age, sex and prior bDMARD (Y/N)), respectively. Results: Median serum drug level at 3 month follow up was 35.0 mg/L (IQR 21.3–45.3) in 116 pts. Response data were available in 110/116 patients. Serum CP level ≥20 mg/L was associated with improvement in ASDAS at 3 months (β=0.55, (95% CI 0.12–1.98), p=0.01). Serum CP level ≥20 mg/L was associated with ASDAS CII at 3 months (OR 3.4 (95% CI 1.0–11.1, p=0.045)). Only 18.2% of pts with CP level <20 mg/L achieved ASDAS CII at 3 months, while 53.2% of pts with CP level 20–40 mg/L and 36.6% with ≥40 mg/L were responders. Conclusions: Serum CP level was associated with clinical response after 3 months of treatment in pts with axSpA. We suggest 20 mg/L as a lower target level for non-trough samples. No additional benefit of having a certolizumab level over 40 mg/L was observed. These results suggest that a therapeutic level of 20–40 mg/L can be implemented in clinical practice for non-trough serum samples in pts with axSpA. Reference: [1] Jani M, et al. Ann Rheum Dis2017;76(1):208–13. Disclosure of Interest: J. E. Gehin Consultant for: Roche, S. Syversen Consultant for: Roche, D. Warren: None declared, G. Goll Consultant for: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, J. Sexton: None declared, E. Strand Consultant for: Pfizer, T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Epirus, Hospira, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, UCB, N. Bolstad Consultant for: Pfizer, Orion Pharma, Napp pharmaceuticals, Takeda, Roche, E. Lie: None declared